По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/9
По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/92)x13x2+xix2 =X,X2(X;+X2)=-3*7=-21
По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/92)x13x2+xix2 =X,X2(X;+X2)=-3*7=-215) (X-X2)2=-2x,x2+x12+x22=6+55=61
Answers & Comments
Ответ:
По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/9
По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/92)x13x2+xix2 =X,X2(X;+X2)=-3*7=-21
По Виету сумма корней равна x1+x2=7, а их произведение x1 *x2=-3, 1) 1/x1+1/x2=(x1+x2)/(x1*x2)=-7/3=-2 1/3 3) x2+x22=(x,+x2)2-2x1*x2=49+6=55 4)x13+x23=(x,+x2) (x2+x22-x, *x2)=7*(55+3)=406 6)1/x12+1/x22=(xi 23)/(x,2*x23)=55/9=6 1/92)x13x2+xix2 =X,X2(X;+X2)=-3*7=-215) (X-X2)2=-2x,x2+x12+x22=6+55=61